Implementation Of Purity K-Means Algorithm In Accident Data Clustering In North Padang Lawas District - Khopipah Parawansah Siregar; Bustami Bustami; Sujacka Retno (Faculty of Engineering, Malikussaleh University, 2024)
Traffic safety is an important issue, especially in areas with high accident rates, such as North Padang Lawas Regency in North Sumatra. This study uses the K-Means Purity Algorithm to group regions based on the level of vulnerability to traffic accidents. The data analyzed includes the number of accidents, deaths, serious injuries, and minor injuries from 2019 to 2023. The results of clustering show that some sub-districts have fluctuating levels of vulnerability. Batang Onang District, for example, was categorized as